Evaluation of blood consumption pattern in Bojnurd Imam Ali Hospital in 2020, North Khorasan province - Javad Hashemi; Saeid Barzegar; Hoseinali Soltani; Ali Nabavi; Mohammadreza Safdari (Golestan University Of Medical Sciences, 2021)
Background and objectives: Blood transfusion has an important role in medical and surgical procedures. In Iran, a person needs blood or blood products every three seconds. Shortage of blood donors, poor facilities for storing and preparing blood products, lengthy preparation process until transfusion as well as irregular use of blood products are some of the important problems associated with blood transfusions. Given the importance of proper and effective use of blood products, this study was carried out to evaluate the blood consumption pattern in Imam Ali Educational, Research and Treatment Center in Bojnurd, Iran. This retrospective study was performed in 2020 on all cases requesting blood products at the Imam Ali Hospital in Bojnurd, Iran. All patient data including age, sex, blood type, requesting ward, type and the number of requested products including packed cell, freshly frozen plasma (FFP) and platelet were extracted from the hospital information system and the daily registry notebooks. Results: Of 3083 blood requests, 58.6% were for males and 41.4% were for females. The most and least requested blood groups were O+ (32.9%) and AB- (0.5%), respectively. Packed cell (27%) and FFP (30%) were the most frequently requested products in the emergency department, while platelets (88.5%) was the most frequently requested product in the oncology department. Cross-matched to transfused blood ratio for packed cell was 1.37. Also, not using blood products index for packed cell, FFP and platelet was 27.5, 0 and 0, respectively. Moreover, transfusion index for packed cell, FFP and platelet were 0.72, 1 and 1, respectively. Conclusion: The pattern of blood consumption in the studied hospital is relatively favorable. However, in some wards such as neurology and burns, there is a need to review the requesting and consumption of blood products. In the case of O - blood type, the probability of not using the requested packed cell and cross-matched is above 50%, which highlights the need for reviewing the blood application process due to the scarcity of this blood type and the imposition of workload. Keywords: Blood Component Transfusion; Blood Cross-matching; Blood Bank; Efficiency of Blood Transfusion